Reconstructing Multicultural Islamic Education in Indonesia (Binoculars of Azyumardi Azra's Thought) - Dwi Mariyono; Maskuri Maskuri; M.Djunaidi Ghony (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Multicultural education is a blessing in disguise for Indonesian pluralism because it promotes diversity and harmony in embroidery. The realization of human and democratic values in it leads to continuity in spreading social piety, universal wisdom, and civilized life. The purpose of this research is to see Aziumardi Azra's thoughts about multicultural education so that the clouds and cloudy skies of education can be opened. At the same time, this paper is dedicated to the extended family of Azyumardi Azra as a teacher of an intellectual multicultural nation. This research is a qualitative research, library research using a philosophical histories approach. The results of the study show that: 1) Azyumardi Azra views multicultural education as an awareness of the recognition and acceptance of diversity as a sunnatullah which should be a pillar of unity. He is so firm in his optimistic foundation to fight for equality, social justice, democracy, tolerance, inclusivity, equality, pluralism, and rule of law for Indonesian people; 2) The application of multicultural education to the history of the Indonesian nation needs to be raised again which was broken by monoculturalism; 3) Multicultural education is the main tool as a media meeting point for a multicultural world nation to prevent social chaos and escapism. 4) Indonesia with all its diversity is a good country because many of its meeting points are based on four foundations, namely Pancasila, NKRI, Unity in Diversity, and the 1945 Constitution. This research is optimistic to simplify the interaction or influence of multicultural values, Indonesian values, and Islamic values on forms of acceptance in Indonesian education